Nebojim sa hovorit´ - Dzurenková, Viktoria (Czech Republic, 2010)
The film follows the life of Margarita Zimamova was formed by two tragic events, her father was executed in the 1950s, and her mother was sentenced to life in prison and later released. As a daughter of political prisoners, Margita had to move from her native Bratislava to the small village of Lovča, where she lives today. In the fight against injustices committed on the same victims of the Communist regime in Slovakia, this determined, enthusiastic and tireless warrior strives to involve everyone, from their closest husband, to people completely unknown.
Verzio Film Festival Submission
Keywords: Documentary films